MENGEMBANGKAN KAPASITAS GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA (PENDAMPINGAN DI MI AL HIDAYAH MARGOREJO SURABAYA) - Lailatul Choiriyah; Lailatu Zahroh (Jurnal Keislaman, 2021)
Capacity building is a process that occurs within the community itself.Outsiders cannot develop people, organizations, or communities, but it is the people,organizations or communities themselves who can develop themselves. Outsiders canonly support by facilitating the process to accelerate their development, and help findaccess to the resources and inputs needed .Currently, improving the quality of learning isthe dream of all teachers. The existence of an active role from all components willrealize learning that is truly quality and also of high quality. The quality of learning canbe realized and achieved when teachers are able to, among others, boost students'learning motivation. Motivation is a psychological condition that encourages someone todo something. Ibtidaiyah madrasas in the city of Surabaya, the majority of their learningquality is still far from expectations; and this is due to the low capacity of teachers.Thus,mentoring at MI Al Hidayah Margorejo Surabaya to develop teacher capacity inincreasing students' learning motivation is urgent and significant in order to equip themto be later applied in learning activities for the convenience of achieving competence forstudents. This assistance can contribute in the form of developing teacher capacity inincreasing student learning motivation at MI Al Hidayah Margorejo Surabaya.